Comparação de dois métodos de elaboração e validação de escala diagramática para a quantificação da severidade da mancha de cylindrocladium em eucalipto - Damasceno, Vítor Flávio Furtado; Furtado, Edson Luiz [UNESP]; Filho, Pedro José Ferreira (FapUNIFESP (SciELO), 2014)
Cylindrocladium leaf spot on Eucalyptus (Myrtaceae) presents high occurrence in the feld, causing losses due to defoliation since the frst year of planting. The need of quantifying the disease and the lack of already published reliable scales have generated the need of elaborating and validating a diagrammatic scale to evaluate Cylindrocladium spp. leaf spot on eucalyptus crops. The study was developed in Botucatu, São Paulo, Brazil, in an E. grandis crop aged approximately two years and showing 2.5 x 3.0 meters spacing under epidemic conditions in the feld. One hundred E. grandis leaves were collected and digitalized by using a scanner, and two scales were elaborated, the frst one performed by AFSoft software to rate colors related to healthy and injured areas and the second one by manual delineating with the aid of a tablet and image treatment on GIMP and ImageJ software. Then, severity was determined based on the sample distribution. For the visual acuity test and validation of scales, leaves were subjected to severity evaluation, without and with scale, by ten raters (fve for each scale), followed by regression analysis. Comparison of scales showed that they can be used to quantify the severity of Cyllindrocladium spp. leaf spot on E. grandis, showing higher accuracy and precision with the second method. AFSoft is indicated for the elaboration of scales with small variation among the sampling tonalities and shorter work time; otherwise, manual delineating by using a tablet is indicated.
Comparison of two methods to elaborate and validate a diagrammatic scale for quantifying the severity of cylindrocladium leaf spot on eucalyptus
Keywords: AFSoft; epidemiology; ImageJ; leaf disease; phytopatometry